Carex section Ammoglochin (Cyperaceae) in Poland - Koopman, Jacob; Więcław, Helena; Kobierski, Piotr (Phytotaxa, 2022)
Species within the Carex section Ammoglochin are difficult to distinguish, due to their similarity and a lack of clear-cut morphological characters. In Poland, all seven European species (Carex arenaria, C. brizoides, C. colchica, C. curvata, C. praecox, C. pseudobrizoides, and C. repens) have been recorded. These taxa can be determined reliably by looking at a combination of characters, especially inflorescence length and colour, gender distribution in the spikes, colour of female glumes, shape, length and width of utricles, and shape of nuts. Carex arenaria, C. brizoides, and C. praecox are the most common Ammoglochin taxa in Poland while C. colchica, C. curvata, and C. pseudobrizoides are much rarer. Carex repens was noted only on a few sites in the central part of the country. In this paper we present a key to identification of the European Ammoglochin species, their description and distribution maps in Poland.